IN TEACHING TRADITIONS OF THE LOCAL SCHOOL OF FINE PROBLEMS AND SOLUTIONS ART IN HIGHER EDUCATION COUNTRIES (World Bulletin of Management and Law, 2023)
Khiva is the introduction and formation of the art of painting as an elective subject for the specialty of fine arts and engineering graphics prepared in higher educational institutions. Introduction and formation of the subject Khiva art of painting was selected in the specialty of Fine Arts and Engineering Graphics prepared in higher education institutions.